LTC 2.0: The 2017 reform of home- and community-based long-term care in Taiwan. Issue 10 (October 2019) - Hsu, Hui-Chuan; Chen, Chen-Fen
Highlights: Taiwan implemented the second long-term care policy project (LTC 2.0). The political party alternation affected the long-term care policy reform. LTC 2.0 focused on home- and community-based long-term care services. The LTC service types and utilization have increased. A new capitalized fee-for-service payment system has been launched. Abstract: Taiwan planned to establish a social insurance-based long-term care system in 2016. However, due to the change in political parties that year, it was decided that Taiwan's long-term care policy would remain a tax-based financing scheme. The new policy focuses on providing home- and community-based service (HCBS); a three-layer HCBS service network within towns and districts was set to provide the 17 types of services in the HCBS spectrum, including preventive care. The reform was criticized as being too restrictive and lacking flexibility. However, the HCBS service spectrum has been widened, the target group has been enlarged, and thus HCBS utilization has increased. A rolling amendment has continued into 2018: the HCBS system requirement has been eased, and a new capitalized fee-for-service payment system has been launched. This paper discusses the analysis of the policy reform.